The Application of Controlled-Source Audio-Frequency Magnetotellurics Numerical Simulations in the Exploration and Electrical Structure Interpretation of the Jinding Lead–Zinc Deposit - Lincheng Zhang; Jingtian Tang; Jiayong Lin; Xiao Xiao (Applied Sciences)
In the field of mineral exploration, geophysical method selection often relies on experience, yet research on ore deposit geophysical models remains insufficient. Addressing this gap, a new exploration model was proposed based on the Jinding lead–zinc mining area, which was integrated as follows: geophysical model–numerical simulation–exploration method selection–field experiments–electrical structure. Firstly, based on geological models and rock–ore resistivity data, a three-dimensional geophysical electrical model of the mining area was constructed for the first time. Secondly, in response to the demands of deep mineral exploration, the CSAMT method with a large exploration depth was initially selected. Then, the coupled finite element–infinite element method was employed to perform forward modeling on the three-dimensional model in order to verify the effectiveness of the CSAMT exploration. Subsequently, the CSAMT exploration experiment was conducted in the Jinding mining area to verify its true effectiveness. During CSAMT data acquisition, high-quality data were obtained through new signal-to-noise ratio experiments and different acquisition time experiments, which built a solid foundation for the reliability of the inversion results. Finally, through CSAMT data processing and inversion interpretation, the electrical distribution at a depth of 1 km below the mining area was obtained. The electrical characteristics of the lithologic system in the mining area were revealed by interpreting the electrical structure characteristics of the survey lines, which provided reliable data support for understanding the geological genesis and metallogenic model in the Jinding lead–zinc deposit. The new exploration model proposed in this study, along with measures to improve data acquisition quality, could serve as a valuable reference for geophysical exploration personnel.